(untitled) (Acta Scientiarum. Health Sciences, 2013)
The community health agents (CHA) are considered health promoters in Brazilian communities teaching them about health promotion and disease prevention, including oral health. According to the Ministry of Health, CHAs must know about seven major oral health issues in Brazil. Thus, the objective of this study was to evaluate the oral health knowledge level of CHAs in the city of Belem, Pará State, Brazil. The study was based on a self-guided script, through a pre-prepared questionnaire containing 16 multiple-choice questions related to oral health knowledge. The survey was conducted with 94 agents from seven Family Health stations featuring oral health teams in Belem. It was concluded that community agents should be better prepared about oral care, as not all oral health issues were known by the CHAs oral health teams in Belem.